2004
DOI: 10.1038/sj.bjc.6601862
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of [18F]fluoroetanidazole as a new marker for imaging tumour hypoxia with positron emission tomography

Abstract: Development of hypoxia-targeted therapies has stimulated the search for clinically applicable noninvasive markers of tumour hypoxia. Here, we describe the validation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 61 publications
0
44
0
1
Order By: Relevance
“…A careful biologic evaluation of 18 F-FETA found that this second-generation agent had potential advantageous physicochemical properties. Most notably it was stable to nonhypoxic degradation in vivo (102)…”
Section: Fluoromisonidazole and Related Nitroimidazoles: Clinical Stumentioning
confidence: 99%
“…A careful biologic evaluation of 18 F-FETA found that this second-generation agent had potential advantageous physicochemical properties. Most notably it was stable to nonhypoxic degradation in vivo (102)…”
Section: Fluoromisonidazole and Related Nitroimidazoles: Clinical Stumentioning
confidence: 99%
“…Reischl et al [165] , Piert et al [166] , Picchio et al [167] , Maier et al [168] , Tran et al [169] Barthel et al [187] Busk et al [170] , Mortensen et al [171] , Piert et al [166] , Tran et al [169] Barthel et al [187] Busk et al [170] , Busk et al [172] , Busk et al [173] , Busk et al [174] , Busk et al [175] , Graves et al [176] , Maier et al [168] , Solomon et al [177] NA Belloli et al [178] , Picchio et al [167] , Troost et al [179] , Valtorta et al [143] NA Sorger et al [57] , Piert et al [166] , Reischl et al [165] Rasey et al [188] Postema et al [180] , Bollineni et al [181] , Trinkaus et al [58] , Verwer et al [59] NA Grosu et al [182] , Souvatzoglou et al [183] , Schuetz et al [184] , Shi et al [106] , Mortensen et al [185] , Havelund et al [186] NA…”
Section: F]ef5mentioning
confidence: 99%
“…[32][33][34] We therefore require both a means of determining the intrinsic values of α, β and γ, and techniques for quantitatively imaging the distribution of clonogenic cell density and of hypoxia. Recent advances in positron emission tomography (PET) and magnetic resonance imaging and spectroscopy, particularly the development of new techniques for imaging tumor cell metabolism 35,36 and hypoxia, [37][38][39][40] show progress towards fulfilling the imaging requirements. Here we present methods for quantifying the intrinsic radiobiological parameters for a specific patient.…”
Section: Iib Radiobiological Modelmentioning
confidence: 99%